¿Por qué las escuelas necesitan un criminólogo escolar? - De la Cruz Piste Pat, Guadalupe (Archivos de criminología, seguridad privada y criminalística, 2022)
The present work has the objective of analyzing two problems that exist in schools and that require the intervention of the school criminologist. The problems presented in this work are two: school violence and bullying; and antisocial and criminal behaviors of adolescents. Statistics indicate a high prevalence of these problems in schools and although there are laws that indicate who and how to proceed in cases of violence; It is the criminologist who must demonstrate with his knowledge and training that he is competent to successfully carry out strategies that allow schools to prevent violence and crime.